STRATEGI INTERNALISASI NILAI-NILAI MODERASI BERAGAMA DI MADRASAH - imawanty; Fiqra; Rais (Yayasan Al-Afif, 2024)
The problem with this research is that the values of religious moderation in madrasahs have not been maximized. This is proven by the many cases of intolerance, radicalism and misrepresentation of other values. The limitations of this research problem are: (1) What is the planning strategy for internalizing the values of religious moderation in madrasas; (2) What is the strategy for organizing the Internalization of Religious Moderation Values in madrasas; (3) What is the Strategy for Implementing the Internalization of Religious Moderation Values in madrasas: (4) How is the Evaluation of the Internalization of Religious Moderation Values in madrasas? The method used is a descriptive qualitative research method with several stages carried out. The source for this research is the research site at Madrasah Aliyah 2 Garut, the research subjects were the head of the madrasah, teachers and students in the MAN 2 Garut environment, while activities related to the implementation of religious moderation were collected from observations, interviews and other supporting documents. The results of this research are (1) The planning strategy for internalizing moderation values is carried out through the socialization of ideas, knowledge and understanding about religious moderation. (2) Organizing religious moderation in the school environment can involve various organizational steps and strategies; (3) Programs implemented regarding religious moderation include holding education and training sessions for students, teachers, staff and parents; (4) Evaluation of the internalization of religious moderation values is carried out through surveys, interviews with students, teachers and Madrasah staff to measure the level of understanding, attitudes and practices related to religious moderation.